Surface Plasmon States in Inhomogeneous Media at Critical and Subcritical Metal Concentrations - Katyayani Seal; Dentcho A. Genov (International Journal of Optics)
Semicontinuous metal-dielectric films are composed of a wide range of metal clusters of various geometries—sizes as well as structures. This ensures that at any given wavelength of incident radiation, clusters exist in the film that will respond resonantly, akin to resonating nanoantennas, resulting in the broad optical response (absorption) that is a characteristic of semicontinuous films. The physics of the surface plasmon states that are supported by such systems is complex and can involve both localized and propagating plasmons. This chapter describes near-field experimental and numerical studies of the surface plasmon states in semicontinuous films at critical and subcritical metal concentrations and evaluates the local field intensity statistics to discuss the interplay between various eigenmodes.